Pengaruh Persepsi, Sikap dan Motivasi Beragama Terhadap Perilaku Konsumen dalam Melaksanakan Ibadah Sholat Saat Berwisata - Riki hanri malau; Muslim muslim; Saipul Al Sukri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Knowing consumer behavior is the most crucial part for companies to attract and win customers. Understanding consumer behavior is not easy. One of the factors that influence a person's behavior is psychological factors. This research is a quantitative descriptive study that in its presentation analyzes and describes descriptively the influence of a person's perception, attitude and religious motivation on his behavior in carrying out prayers while traveling. The research data was obtained by distributing questionnaires to 96 respondents determined by purposive sampling. While the data analysis using multiple linear regression, which was processed using SPSS 21 software. The study results revealed that consumer psychological factors in the form of perceptions, attitudes and motivations together had a positive effect on the behavior of Muslim tourists to pray while traveling. From the research results, it is hoped that this study can encourage the halal tourism industry players to pay attention to additional and supporting facilities so that the length of stay of tourists is better.